Glycemic control in women with GDM: insights from a randomized controlled pilot trial on plant-based Nordic healthy diet versus moderately carbohydrate restricted diet - Lisa Torsdatter Markussen; Jemina Kivelä; Jaana Lindström; Miina Ollikainen; Mikko Kytö; Seppo Heinonen; Saila Koivusalo; Jelena Meinilä (BMC Nutrition)
Abstract Background Gestational Diabetes Mellitus (GDM) prevalence is rising worldwide, but optimal dietary strategies remain unclear. The eMOM pilot RCT compared a plant-protein rich Healthy Nordic Diet (HND) and a moderately carbohydrate restricted diet (MCRD) and their potential effects on time in glucose target range (≤ 7.8 mmol/L, %TIR), and on newborn body composition. Methods Forty-two participants were randomized to either HND (n = 20) or MCRD (n = 22) face-to-face nutritional counseling from gestational weeks (GW) 24 + 0—28 + 6 (baseline) until delivery. The HND intervention had no restriction in carbohydrate intake and emphasized plant-based protein sources and Nordic food, while the MCRD had a moderate carbohydrate restriction (~ 40% in proportion to total daily energy consumption, E%). Continuous glucose monitoring was worn for 14 days to assess glucose levels and %TIR. Blood samples for glucose and lipid metabolism and 3-day food diaries were collected at baseline and at GW 34 + 0—35 + 6. Neonatal body composition was measured by air displacement plethysmography. Difference between groups were analysed with t-test and Wilcoxon test. Results Thirty-two women completed the study. Both groups maintained the %TIR during majority of the time (98.9 and 99.3% for MCRD and HND respectively, p = 0.921) in GW 34 + 0 – 35 + 6. The mean glucose was lower in the MCRD group compared to the HND group (5.0 SD 1.03 vs. 5.2 SD 0.96 mmol/l, p < 0.001). No differences were observed in glucose variability, lipid metabolism, gestational weight gain, or in the body composition of the newborns. HND had lower diet macronutrient adherence than the MCRD, resulting in similar macronutrient composition in both groups. The mean macronutrient intakes were fat: 40.6 vs. 39.5 E%, carbohydrate: 40.5 vs. 42.4 E%, protein: 18.9 vs. 18.1 E% for the MCRD and HND groups, respectively. The HND decreased intake of meat and increased fish consumption significantly compared to the MCRD. Conclusions Both a moderately restricted carbohydrate diet and a diet focused on plant-based protein effectively maintained a large time within the treatment target range in women with GDM. Further research could explore the impact of protein quantity and sources in maternal diets on glycemic control and newborn outcomes. Trial registration The eMOM pilot trial is registered in Clinicaltrials.gov (21/09/2018, NCT03681054).